2017
DOI: 10.1021/jacs.7b11663
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Dearomative syn-1,4-Carboamination

Abstract: A dearomative 1,4-carboamination of arenes has been achieved using arenophile cycloaddition and subsequent palladium-catalyzed substitution with non-stabilized lithium enolates. This protocol delivers products with exclusive syn-1,4-selectivity and can be also conducted in an asymmetric fashion. The method allows rapid dearomative difunctionalization of simple aromatic compounds into functional small molecules amenable to further diversification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…We suspected the product might be labile, resulting in a relatively lower yield. Gratifyingly, substrates bearing a series of substituents on the indole ring or the aryl bromide ring could be converted into the corresponding products in moderate yields (56)(57)(58)(59)(60)(61)(62)(63)(64)(65). It should be mentioned, generally about 5% of arylcarboxylation of indole's C2-C3 double bond and/or about 5% of direct debromination side products were also observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspected the product might be labile, resulting in a relatively lower yield. Gratifyingly, substrates bearing a series of substituents on the indole ring or the aryl bromide ring could be converted into the corresponding products in moderate yields (56)(57)(58)(59)(60)(61)(62)(63)(64)(65). It should be mentioned, generally about 5% of arylcarboxylation of indole's C2-C3 double bond and/or about 5% of direct debromination side products were also observed.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, visible-light photoredox catalysis [35][36][37][38][39][40][41][42][43][44] has emerged as a promising strategy for developing mild protocols for dearomatization, [45][46][47][48][49][50][51][52][53][54][55][56][57][58] including several significant protocols for the dearomatization of nonactivated arenes, [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] such as dearomative cycloadditions mainly from the groups of Sarlah and Bach, [59][60][61][62] and oxidative dearomatization. [63][64][65] A distinct redox-neutral hydroalkylative dearomatization of naphthalene derivatives was also reported by the group of Zhang, Mei and You.…”
Section: Introductionmentioning
confidence: 99%
“…The observed stereoselectivity was in accordance with the general trends of transition metal catalyzed allylic substitution . For example, Grignard reagents were amenable to the Ni‐catalyzed anti ‐1,2‐carboamination, while Li enolates and amines provided syn ‐1,4‐aminofunctionalization under Pd catalysis.…”
Section: Figurementioning
confidence: 99%
“…Within the last decade, visible‐light has been used as a green and sustainable energy to drive diverse chemical reactions . Of particular note, the groups of Sheridan, Sarlah, Glorius, and Bach independently reported that dearomative cycloaddition of arenes with arenophiles or alkenes could be achieved by exploiting visible‐light induced excited state reactivity . As a distinct reactivity mode, visible‐light photoredox catalysis has also provided a mild strategy for single‐electron approaches.…”
Section: Introductionmentioning
confidence: 99%